Perancangan UI/UX Pada Aplikasi Nutrizecom Dengan Metode Design Thinking - Nadiya Rahmawati; Ajeng Rohani Ridwansyah; Chandra Dinata; Nabila Savitri; Natasya Herdiana; abdul rahman (Universitas Multi Data Palembang, 2022)
Abstract: not a few people order food directly or come to the sellers place, most people prefer to order online through a food application because it makes it easier for some people who are busy working or doing other activities. These people really benefit from this situation, because it can save time. where there are not many online food applications that provide food menus for those who are on a diet. therefore UI/UX needs to be developed. In the application that we developed called